ЧЕТ ТИЛЛАРНИ ЎҚИТИШДА ЗАМОНАВИЙ УСЛУБЛАР - Buronova, Shaxnoza (Maktabgacha taʼlim jurnali, 2021)
This article is devoted to modern methods of teaching foreign languages ​​about the main methods of teaching English